2012
DOI: 10.1007/978-3-642-28798-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation: Data Integration Tools Meet the Semantic Web (Experiences from the Ondex Project)

Abstract: Abstract-More information is now being published in machine processable form on the web and, as de-facto distributed knowledge bases are materializing, partly encouraged by the vision of the Semantic Web, the focus is shifting from the publication of this information to its consumption. Platforms for data integration, visualization and analysis that are based on a graph representation of information appear first candidates to be consumers of web-based information that is readily expressible as graphs. The ques… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The new format will be both a reference for converting external data of interest into a unified data format, and a source of queries, data access and exchange for applications. We have achieved a first concrete result by reviewing past work [59], and developing an Ondex plug-in to export OXL data as RDF that instantiates our ontology [60].…”
Section: Architecture and Implementationmentioning
confidence: 99%
“…The new format will be both a reference for converting external data of interest into a unified data format, and a source of queries, data access and exchange for applications. We have achieved a first concrete result by reviewing past work [59], and developing an Ondex plug-in to export OXL data as RDF that instantiates our ontology [60].…”
Section: Architecture and Implementationmentioning
confidence: 99%
“…NoSQL approaches, together with semantic web applications, more recently gained popularity in the life sciences ( 22 ), e.g. as Key-Value Stores, BigTable ( 23 ), document databases, triple stores or graph databases ( 24 ).…”
Section: A Graph Database For Simulation Models and Associated Datamentioning
confidence: 99%
“…The scripting syntax is based on a bespoke language developed in Lysenko 2012. Ondex networks can be exported in several formats such as the Ondex exchange format OXL (Taubert et al, 2007), RDF (Splendiani et al, 2012) or Cytoscape-compatible JSON. Networks can be visualised and inspected using tools like Cytoscape (Shannon et al, 2003) or in the Ondex User Interface (Ondex UI) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a Cytoscape plugin, called OndexView allows for concise graphical representations of integrated knowledge networks (Weile et al, 2011). Some studies were undertaken to evaluate the utility of semantic web technologies (RDF, SPARQL) within the umbrella of Ondex (Splendiani et al, 2012, Canevet et al, 2010). Two studies showed the contributions of Ondex towards Bayesian data integration (Weile et al, 2012) and towards logic-based modelling (Lesk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%